OPTIMIZING STRATEGY TO IMPROVE EFFECTIVENESS OF DIGITAL MARKETING IN THE B2B FOOTWEAR INDUSTRY (CASE STUDY: PT. ADI PRADANA INTERNASIONAL) - Saarah Yurva Salsabila (CV. Radja Publika, 2025)
Abstract In 6 months, the digital marketing strategy has been implemented, and there have been 330 prospective customers contacted. However, only three customers collaborate with PT. Adi Pradana Internasional. Four customers were in the online meeting stage via Zoom with PT. Adi Pradana Internasional. This study aims to find external factors that significantly impact the effectiveness and optimization of digital marketing approaches in the B2B footwear sector and to identify key features and limitations of this company’s current digital marketing strategy to find a digital marketing optimization approach that the company can implement. This study uses a framework where market competition, social media capability, analytics, and content marketing contribute to optimizing digital marketing. Several analysis methods have been used to optimize the strategy: PESTLE, Porter’s Five Forces, Competitor Analysis, Consumer analysis, Value chain analysis, STP analysis, and VRIO analysis. SWOT analysis identifies strengths, weaknesses, opportunities, and threats. Development from the SWOT analysis was conducted by using the TOWS matrix. PT. Adi Pradana Internasional needed to make KPIs for digital marketing content, monitor KPIs, improve social media content, and select a marketing team leader. Keywords: Digital Marketing, Effectiveness, External Analysis, Internal Analysis, Optimization.